Revision of the genus Sulciclivina Balkenohl, 2022 from Asia (Coleoptera, Carabidae, Clivinini) - Balkenohl, Michael (European Journal of Taxonomy, 2023)
The Oriental genus Sulciclivina is revised based on 770 specimens. Sulciclivina attenuata attenuata (Herbst, 1806), S. bhamoensis (Bates, 1892), S. striata striata (Putzeys, 1846), S. sulcigera (Putzeys, 1866), and S. sagittaria sagittaria (Bates, 1892) are redescribed. In order to maintain stability of the nomenclature, lectotypes have been designated for S. attenuata attenuata, S. bhamoensis, S. striata striata, and S. sagittaria sagittaria. The following twelve new taxa are described: S. attenuata semireticulata subsp. nov., S. striata kottea subsp. nov., S. coxisetosa sp. nov., S. basiangusta sp. nov., S. splendida sp. nov., S. mikirensis sp. nov., S. karelkulti karelkulti sp. nov., S. karelkulti medanensis subsp. nov., S. curvata sp. nov., S. oculiangusta sp. nov., S. andrewesi sp. nov., and S. sagittaria singaporensis subsp. nov. An identification key to the species is provided which includes the characterization of the two new species groups attenuata and sagittaria. All taxa are figured including male and female genitalia, if available. The available faunistic information is provided, and distribution records are displayed on a map.